2011
DOI: 10.1186/1756-0500-4-66
|View full text |Cite
|
Sign up to set email alerts
|

The effect of 5-aminolevulinic acid on cytochrome c oxidase activity in mouse liver

Abstract: Background5-Aminolevulinic acid (ALA) is a precursor of heme that is fundamentally important in aerobic energy metabolism. Among the enzymes involved in aerobic energy metabolism, cytochrome c oxidase (COX) is crucial. In this study, the effect of ALA on cytochrome c oxidase activity was measured.Findingsc57BL/6N species of mice were administered ALA orally for 15 weeks. After ALA administration, mice were sacrificed and livers were obtained. COX activity in mitochondria from ALA-administered mouse livers was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
74
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 74 publications
(82 citation statements)
references
References 25 publications
8
74
0
Order By: Relevance
“…2), supporting a stimulating effect on oxidative phosphorylation. This result is consistent with the result from our previous study, where COX expression in mouse liver was increased following ALA administration (8). In addition, oxygen consumption was significantly higher following ALA exposure (Fig.…”
Section: Impact Of Ala On the Warburg Effect In A549 Cellssupporting
confidence: 83%
See 2 more Smart Citations
“…2), supporting a stimulating effect on oxidative phosphorylation. This result is consistent with the result from our previous study, where COX expression in mouse liver was increased following ALA administration (8). In addition, oxygen consumption was significantly higher following ALA exposure (Fig.…”
Section: Impact Of Ala On the Warburg Effect In A549 Cellssupporting
confidence: 83%
“…To our knowledge, this is the first in vitro study showing that ALA causes tumor apoptosis via enhancement of oxidative phosphorylation. In a previous study, we showed that in mouse liver, ALA increases the expression and activity of COX, which is an indicator of oxidative phosphorylation (8). The present study goes further by showing that ALA affects both aspects of the Warburg effect by increasing oxidative phosphorylation and suppressing glycolysis.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…The biological effect of administration of the heme precursor 5-ALA is not only high accumulation of PpIX within the mitochondria of tumor cells, but also generation of antitumor immunity via activation of heat-shock protein as well as inhibition of heme-oxygenase-1 with photoactivation and hyperthermia (26). Moreover, recent studies have reported that 5-ALA can improve the function of the mitochondrial respiratory chain (particularly COX activity) and thereby disrupt the warburg effect and induce caspase-dependent apoptosis in tumor cells (27,28). In our previous study, we demonstrated that multi-dose ionizing radiation induced strong aggregation of activated macrophages with phagocytic features within tumors, causing strong inhibition of tumor growth in glioma cells in vivo (19).…”
Section: -Ala Acts As a Radiosensitizer Via The Enhancement Of Delaymentioning
confidence: 99%
“…This delayed ROS production is induced primarily in the mitochondria of tumor cells (24,25). Meanwhile, the heme precursor 5-ALA presents not only a high accumulation of PpIX in the mitochondria of tumor cells, but also improves dysfunction of the mitochondrial respiratory chain in tumor cells (26)(27)(28). Thus, we hypothesized that 5-ALA-induced PpIX may operate upon mitochondria, and cause changes in delayed production of ROS after ionizing irradiation in tumor cells.…”
Section: -Aminolevulinic Acid Strongly Enhances Delayed Intracellulamentioning
confidence: 99%